Tests in tension-torsion conditions with descending sections of strain curve construction - M.P. Tretiakov; V.E. Vildeman (Fracture and Structural Integrity)
The paper is devoted to theoretical and experimental investigation of materials behavior on postcritical deformation stage (strain softening). Tests results, which confirm theoretical justification of specimen configuration impact on the possibility of creating descending sections of strain curve, are given. It is shown that, with sufficient stiffness of loading system, equilibrium postcritical deformation of materials is possible. It is confirmed in uniaxial tension tests with unloading on postcritical deformation stage. Test results on tension with torsion of thin-walled tubular specimens in strain softening conditions are adduced.